1979
DOI: 10.1126/science.572083
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Amnesia for Old (Reactivated) Memory: Some Anomalous Characteristics

Abstract: Old memory, when reactivated by cue exposure, was disrupted by mild or deep hypothermia treatments. New memory was impaired only by deep cooling. Moreover, old but not new learning showed spontaneous recovery. Old reactivated memory may be qualitatively different from newly acquired memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
112
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(122 citation statements)
references
References 28 publications
7
112
3
Order By: Relevance
“…Several groups have observed recovery of memory following post-retrieval retention performance impairment within hours, days, or weeks (Mactutus et al 1979;Vianna et al 2001;Anokhin et al 2002;Bahar et al 2004;Lattal and Abel 2004;Power et al 2006), suggesting that the retention performance impairment induced by post-retrieval treatment may be temporary. This is consistent with the interpretation that such treatments may temporally disrupt memory retrieval (Riccio et al 2002;Arshavsky 2003;Lattal and Abel 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have observed recovery of memory following post-retrieval retention performance impairment within hours, days, or weeks (Mactutus et al 1979;Vianna et al 2001;Anokhin et al 2002;Bahar et al 2004;Lattal and Abel 2004;Power et al 2006), suggesting that the retention performance impairment induced by post-retrieval treatment may be temporary. This is consistent with the interpretation that such treatments may temporally disrupt memory retrieval (Riccio et al 2002;Arshavsky 2003;Lattal and Abel 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Rats were not able to cross between compartments, as the guillotine door was closed at all times. The parameters chosen for memory reactivation (15 sec) and extinction (12 min) were similar to those of previous studies (Hinderliter and Riccio 1977;Mactutus et al 1979;Morgan and Riccio 1994;Harrod et al 1996;Briggs and Riccio 2007). Two fear control groups did not receive extinction, but were merely tested to evaluate the level of fear without any reexposure treatment.…”
mentioning
confidence: 91%
“…A challenge to the consolidation view comes from findings that memories previously stored or consolidated could once again become labile and susceptible to disruption following reactivation (Misanin et al 1968;Mactutus et al 1979;Nader et al 2000; for review, see Riccio et al 2006). It is hypothesized that when a previously formed memory is reactivated by a reminder cue it goes through a reconsolidation process, which puts the memory in a labile state before again becoming consolidated.…”
mentioning
confidence: 99%
“…Numerous control procedures assured that the specific cues associated with the original learning were essential to the effect and not merely a reinstatement of an emotional or motivational state, as had been suggested by other investigators Robbins and Meyer 1970). Hypothermia-induced amnesia for a well-trained task was obtained after exposure of the rat to either the unconditioned stimulus (UCS) (foot shock) or the context and UCS, immediately before the amnestic treatment (Mactutus et al 1979;Richardson et al 1982). These researchers even found that reactivated memories were more susceptible to the hypothermic treatment than newly acquired memories, in that less cooling was required to obtain amnesia after reactivation.…”
Section: Reactivation and Experimental Amnesiamentioning
confidence: 99%